2016
DOI: 10.1631/jzus.b1500250
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic properties of lactic acid bacteria isolated from traditionally fermented Xinjiang cheese

Abstract: Abstract:Six lactic acid bacterial (LAB) strains were isolated from traditionally fermented Xinjiang cheese and evaluated for functional and probiotic properties and potentials as starter cultures. The isolated six LAB strains comprised Lactobacillus rhamnosus (one strain), Lactobacillus helveticus (one strain), and Enterococcus hirae (four strains). All of the six strains were tolerant to acidic and bile salt conditions. Among which, the L. rhamnosus R4 strain showed more desirable antimicrobial, auto-aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 45 publications
5
70
1
1
Order By: Relevance
“…in this study, all tested strains indicated a proportion of growth above 69.8% in the present bile salt 0.3%, which demonstrated good bile salt tolerance. These results were consistent with previous study [3,9,11]. To further investigate the safety and functional characteristic of these strains as probiotic, tests were conducted to assess their antimicrobial activity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…in this study, all tested strains indicated a proportion of growth above 69.8% in the present bile salt 0.3%, which demonstrated good bile salt tolerance. These results were consistent with previous study [3,9,11]. To further investigate the safety and functional characteristic of these strains as probiotic, tests were conducted to assess their antimicrobial activity.…”
Section: Discussionsupporting
confidence: 90%
“…Tolerance to acidic condition is the most commonly used method to detect the viability and activity of probiotic bacteria in the small intestine and stomach. According to a previous study [3,10]. The survival rate at pH 2 is considered as optimal acid tolerance for selected probiotic strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These home-made products are fermented spontaneously by natural starter cultures from previous batches having complex microbial compositions (Hu et al, 2015;Azat et al, 2016). Understanding the microbial diversity and dynamics of these starters is important for the standardization of Chinese traditional fermented milk products.…”
Section: Fermented Dairy Productsmentioning
confidence: 99%